Efficacy and safety of oral protein-containing carbohydrate supplements for enhancing recovery after elective surgery : a systematic review - Pretorius, Jane (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNutr)--Stellenbosch University, 2021.